Pengaruh Konservatisme Akuntansi, Intellectual Capital, dan Leverage terhadap Kinerja Keuangan: Studi pada Perusahaan Sektor Consumer Cyclicals yang Terdaftar di Bursa Efek Indonesia Periode 2022-2024 - Yalni, Nadia Putri; Mulyani, Erly (Jurnal Eksplorasi Akuntansi, 2026)
This study aims to examine the effect of accounting conservatism, intellectual capital, and leverage on financial performance. This study is a quantitative study. The population used in this study are consumer cyclicals sector companies listed on the Indonesia Stock Exchange for the period 2022-2024. The sampling technique used purposive sampling, resulting in a sample of 86 companies. The data source in this study ware secondary data in the form of annual reports. The data analysis method used was multiple linear regression analysis. The results showed that accounting conservatism and leverage did not affect financial performance. Meanwhile, intellectual capital had a positive and significant effect on financial performance.